The intimate affliction of vicarious racialization: Afro-Chinese couples in South China. - Wang, Wei; Hoang, Andrew Pau; Jordan, Lucy Porter (Inter-Asia Cultural Studies, 2023)
Racial prejudice and discrimination towards Africans in Guangzhou have been widely documented and are systemic. Nonetheless, conjugal unions and family formation between Chinese citizens and members of the African diaspora have become more prevalent in recent years. Together, Afro-Chinese couples confront quotidian threats of violence, arrest, and deportation of the African partners, which threats affect their families and livelihoods. Studies thus far have neglected the complex dynamics and negotiations of racism that manifest in the interracial domestic sphere. Through reflexive observational fieldwork and qualitative interviews, this study provides a contemporary analysis of negotiating racism in intimate family life, especially from the unique standpoint of the Chinese spouse in an Afro-Chinese marriage. Drawing upon empirical data and the Althusserian notion of interpellation, we develop the concept of the intimate affliction of vicarious racialization to analyze how multiple inequities intersect and condition the couples' overlapping lived experiences. Vicarious racialization particularly emphasizes processes by which Chinese women become interpellated but also resist anti-Black racism. This intimate affliction destabilizes the prevailing discourse on racism, which focuses on targeted (racialized) minorities, and the dichotomy of direct/indirect discrimination against them. This study highlights the often-overlooked role of women's agency across multiple borderlands with their partners as they negotiate gendered, racialized, and classed subjections in familial and social spaces.